1990
DOI: 10.1111/j.1365-2958.1990.tb00607.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation potassium efflux from Escherichia coli by glutathione metabolites

Abstract: The mechanism by which N-ethylmaleimide (NEM) elicits potassium efflux from Escherichia coli has been investigated. The critical factor is the formation of specific glutathione metabolites that activate transport systems encoded by the kefB and kefC gene products. Formation of N-ethyl-succinimido-S-glutathione (ESG) leads to the activation of potassium efflux via these transport systems. The addition of dithiothreitol and other reducing agents to cells reverses this process by causing the breakdown of ESG and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
121
0
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 77 publications
(126 citation statements)
references
References 22 publications
4
121
0
1
Order By: Relevance
“…We have previously shown that the involvement of glutathione in the NEMactivation of K+ efflux can be demonstrated by converting the glutathione pool to S-carboxymethylglutathione by treatment with iodoacetate. S-Carboxymethylglutathione is not a strong activator of the E. coli KefC system and subsequent incubation with NEM does not elicit K+ efflux because there is no free glutathione to react with NEM and form ESG (Elmore et al, 1990). Re-incubation of iodoacetate-treated E. coli cells with glutathione leads to the re-establishment of the cytoplasmic glutathione pool and restoration of sensitivity of K+ efflux to NEM (Elmore et al, 1990).…”
Section: Involvement Of Glutathione In Nem-activated K+ Efluxmentioning
confidence: 98%
See 4 more Smart Citations
“…We have previously shown that the involvement of glutathione in the NEMactivation of K+ efflux can be demonstrated by converting the glutathione pool to S-carboxymethylglutathione by treatment with iodoacetate. S-Carboxymethylglutathione is not a strong activator of the E. coli KefC system and subsequent incubation with NEM does not elicit K+ efflux because there is no free glutathione to react with NEM and form ESG (Elmore et al, 1990). Re-incubation of iodoacetate-treated E. coli cells with glutathione leads to the re-establishment of the cytoplasmic glutathione pool and restoration of sensitivity of K+ efflux to NEM (Elmore et al, 1990).…”
Section: Involvement Of Glutathione In Nem-activated K+ Efluxmentioning
confidence: 98%
“…The activation of the KefC system can be achieved by the reaction of N-ethylmaleimide (NEM) with cellular glutathione to form the activator N-ethylsuccinimido-S-glutathione (ESG) (Elmore et al, 1990). We therefore sought to elicit K+ efflux from a range of bacteria by the addition of NEM (0.5 mM final concentration) to cells washed and suspended in K+-free medium (Fig.…”
Section: Activation Of K + Egux By N-ethylmaleimidementioning
confidence: 99%
See 3 more Smart Citations